Who's Taking What? "Applied STEM" Coursetaking for High School Students With Learning Disabilities. (March 2021) - Gottfried, Michael A.; Plasman, Jay; Freeman, Jennifer A.; Dougherty, Shaun
Increasing and improving the science, technology, engineering, and mathematics (STEM) educational pipeline has been a point of emphasis for decades, and federal policy in the United States has urged high schools to embed new types of STEM courses into the curriculum. As one example, applied STEM courses—one growing branch within career and technical education (CTE)—are designed to reinforce traditional academic STEM content and to motivate students' interests and long-term pursuits in STEM areas. That said, little is known about who takes these courses, and applied-STEM-CTE enrollment in these courses has not been explored in the research for students with learning disabilities. Using the High School Longitudinal Study (a nationally representative data set of high school students), we asked whether CTE coursetaking differed for students with learning disabilities compared with those without disabilities, and whether there were specific coursetaking differences in applied-STEM-CTE. We found that students with learning disabilities were more likely to earn more units in CTE courses compared with students without disabilities. Yet, when looking at applied-STEM-CTE courses, we see that although students with learning disabilities earn more CTE units than students without disabilities, students with learning disabilities do not take different amounts of applied-STEM-CTE courses. Implications are discussed.